The Chip and The Pale Truth by V. Zazubrin and Chocolate by A. Tarasov-Rodionov as “irrelevant” works: to the problem of “Red Terror” in the literature 1920s - Proskurina, Elena (Literatūra, 2019)
In the article, the problem of «red terror» is revealed in a little-known material. The story of the Siberian writer V. Zazubrin (1895–1937) The Pale Truth (1923) was published only once in Soviet times – in 1923 in the journal “Siberian Lights”; the novella “Sliver” (1923) was not published during the life of the author and was first published only in 1989. The story of A. Tarasov-Rodionov (1885–1938) Chocolate (1922) was reprinted several times in the 1920s, after which it was forgotten for decades. The work traces the history of the creation of the Chip, which until now contains many “white spots”. The originality of the plot is revealed, in which the image of the main character contradicts the canon of the “iron knight of the revolution”: tired of his firing “hard work”, he is going crazy. The typological similarity of the Chip with the story Chocolate is shown, the plot of which is also based on the dramatic story of the hero. Particular attention is paid to the receptive dialogue of the story The Pale Truth notch with Chocolate: in both works, heroes devoted to the cause of the revolution become its innocent victims. Both works echo and, in their pathos of justifying the “Red Terror”, the idea of “the future of beautiful humanity”. In terms of creative reception, the plot rolls of The Pale Truth with Chocolate, similarities in the images of the main characters and individual elements of poetics are shown. The “irrelevance” of Zazubrin and Tarasov-Rodionov’s works for Soviet literature is substantiated. The main factor is the discrepancy between their plots and the leading ideological maxims of the era.